2022
DOI: 10.21608/ajs.2022.92048.1410
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Of Rhizoctonia Solani Growth and Its Extracellular Hydrolytic Enzymes by Different Extracts of Cinnamon (Cinnamomum Cassia) and Black Cumin Seeds (Nigella Sativa)

Abstract: The present study evaluated the ability of different extracts of cinnamon and black cumin seeds to inhibit the growth of the phytopathogenic fungus Rhizoctonia solani and its extracellular cell wall degrading enzymes. Concentrations of 300 and 450 ppm of methylene chloride and hexane extracts of cinnamon completely inhibited the growth of R. solani after 72 hours of incubation at 25±1°C in vitro. Methylene chloride or hexane extracts of black cumin seeds at 4000 ppm after 72 hours inhibited the growth of R. so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, several studies have demonstrated that black cumin seeds have an inhibitory effect on different types of proteases including the phytopathogenic fungi R. solani extracellular protease. It has been reported that black cumin seeds' methanolic extract at 2000 ppm inhibited 74% of R. solani protease activity [15]. Moreover, it has been reported that black cumin seeds' oil inhibited 75.4% and 91.1% of the serine protease elastase type I and type II activity, respectively, and 92.4% of collagenase activity at a concentration of 300 µg/mL [16].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, several studies have demonstrated that black cumin seeds have an inhibitory effect on different types of proteases including the phytopathogenic fungi R. solani extracellular protease. It has been reported that black cumin seeds' methanolic extract at 2000 ppm inhibited 74% of R. solani protease activity [15]. Moreover, it has been reported that black cumin seeds' oil inhibited 75.4% and 91.1% of the serine protease elastase type I and type II activity, respectively, and 92.4% of collagenase activity at a concentration of 300 µg/mL [16].…”
Section: Introductionmentioning
confidence: 98%